2010
DOI: 10.1590/s0100-204x2010000100013
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade, desempenho e características morfofisiológicas do trato digestório de leitões desmamados sob dietas com mananoligossacarídeo

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da adição do prebiótico mananoligossacarídeo (MOS) nas dietas de leitões sobre a digestibilidade dos nutrientes, o desempenho e as características morfofi siológicas do trato digestório. No primeiro experimento, foram utilizados 16 leitões com peso de 24,8±2,79 kg. Utilizou-se o método de coleta total de fezes para determinar a digestibilidade das rações controle e com 0,5% de prebiótico. No segundo experimento, avaliaram-se o desempenho e a incidência de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
4
0
7
Order By: Relevance
“…Evaluating the effect of antibiotics and different inclusion levels of MOS (0.25%, 0.50%, or 0.75%) in the diets of piglets from 22 to 63 days of age, Santos et al (2010) also observed no effect on VH. However, GHELER et al (2009), in a study with benzoic acid (0.25; 0.50, or 0.75%), observed an increase in VH at all levels of inclusion compared to the control diet.…”
Section: Resultsmentioning
confidence: 95%
“…Evaluating the effect of antibiotics and different inclusion levels of MOS (0.25%, 0.50%, or 0.75%) in the diets of piglets from 22 to 63 days of age, Santos et al (2010) also observed no effect on VH. However, GHELER et al (2009), in a study with benzoic acid (0.25; 0.50, or 0.75%), observed an increase in VH at all levels of inclusion compared to the control diet.…”
Section: Resultsmentioning
confidence: 95%
“…Zhao et al (2012) reported higher feed intake in pigs fed mannan-oligosaccharide diets (0.5%). In contrast, Boas et al (2016), working with a mixture (0.5%) of lactic, formic, and citric acids; Walsh et al (2012), with (2.58 mL L 1 ) propionic, acetic, and benzoic acid; and Santos et al (2010) and Marinho et al (2007), with mannan-oligosaccharide (inclusion levels from 0.2 to 0.75%), did not observe an effect of additives on feed intake. In summary, the effects of organic acids and prebiotics such as mannanoligosaccharide on growth performance are credited to the improvement in nutrient utilisation of the diet and not to an increase in feed intake.…”
Section: Discussionmentioning
confidence: 81%
“…The effect of the use of prebiotics for growth, feed intake, and feed efficiency shows a varied response and did not influence piglet performance during the nursery period, for prebiotics such as mannooligosaccharides (CORASSA et al, 2012;SANTOS et al, 2010;SILVA et al, 2012), fructoligossacharides (VISENTINI et al, 2008), and chitooligossacharides (CHEN et al, 2009). However, with COS, some studies have reported better growth and feed efficiency in broilers (HUANG et al, 2005;LI et al, 2007) and piglets Apical villi necrosis 3 0 a 3…”
Section: Resultsmentioning
confidence: 99%